Potentials of endogenous neural stem cells in cortical repair - Saha, Bhaskar; Jaber, Mohamed; Gaillard, Afsaneh (Frontiers in Cellular Neuroscience, 2012)
In the last few decades great thrust has been put in the area of regenerative neurobiology research to combat brain injuries and neurodegenerative diseases. The recent discovery of neurogenic niches in the adult brain has led researchers to study how to mobilize these cells to orchestrate an endogenous repair mechanism. The brain can minimize injury-induced damage by means of an immediate glial response and by initiating repair mechanisms that involve the generation and mobilization of new neurons to the site of injury where they can integrate into the existing circuit. This review highlights the current status of research in this field. Here, we discuss the changes that take place in the neurogenic milieu following injury. We will focus, in particular, on the cellular and molecular controls that lead to increased proliferation in the Sub ventricular Zone (SVZ) as well as neurogenesis. We will also concentrate on how these cellular and molecular mechanisms influence the migration of new cells to the affected area and their differentiation into neuronal/glial lineage that initiate the repair mechanism. Next, we will discuss some of the different factors that limit/retard the repair process and highlight future lines of research that can help to overcome these limitations. A clear understanding of the underlying molecular mechanisms and physiological changes following brain damage and the subsequent endogenous repair should help us develop better strategies to repair damaged brains.